The wobblies of the Chilean section facing the process of institutionalization of the tenant movement (1924-1926) - Mardones Fabio, Felipe (Revista de Historia Social y de las Mentalidades, 2025)
The present article deals with the link between the Chilean section of the Industrial Workers of the World (IWW) and the tenants' movement in the mid 1920's. The research aims to discuss historical interpretations that associate anarchism with rigidity and irrationality, which would have led to the failure of the anarchist movement. The research aims to discuss the historical interpretations that associate anarchism with rigidity and irrationality, an issue that would have led the anarchist movement to failure. However, it is argued that the anarchist movement was not homogeneous, and in that heterogeneity burst the wobblies, who became active actors in the process of mobilization and social legislation around popular housing. The text underlines the dispute around the process of institutionalization of the tenant movement that the Chilean section of the IWW tried to promote, defending the protagonism of the grassroots and direct action against the coercion and consensus devices imposed by the State. This perspective is nourished by political history, in permanent dialogue with social history, and seeks to break with the prejudices and commonplaces that certain historiography of anarchism has instituted.
Keywords: anarchism; industrial workers of the world; tenant´`'s movement; institutionalization